The Theory and Practice of Apolitical Literature: Die Kolonne, 1929-1932 - Joseph P. Dolan (Studies in 20th & 21st Century Literature, 1977)
The apolitical attitudes that made inner emigration possible were well established in Germany in the decade preceding 1933. Three main ideas from the tradition of "inwardness" were used to justify the exclusion of politics from literature: the timelessness of the inner life, the notion of the genius as hero of society, and the religious function of art. These ideas were propagated especially by the Dresden literary journal, Die Kolonne (1929-1932), to which such leading poets as Günter Eich, Peter Huchel, and Elisabeth Langgässer contributed. Literature of the period reveals a preference for the themes of nature and of myth, insofar as these express the cyclical renewal of the cosmos, and for the motifs of childhood and of cultural pessimism. Apparently apolitical writers were actually politically conservative, and in at least one case, conservatism was associated with an authoritarian upbringing. This link may help explain the extraordinary survival of apolitical attitudes beyond 1945.
Keywords: Die Kolonne; apolitical; conservative; nature; myth; inwardness